A Greener Future using Machine Learning: Transforming the Environment in Big Cities - MOGOȘ, Radu-Ioan; DOBREA, Răzvan-Cătălin; CREȚU, Raluca-Florentina; PĂCURAR, Gheorghe (European Journal of Sustainable Development, 2025)
One of the main elements that influences daily life is the environment. Especially in big cities, it leaves an important mark on the quality of life of its inhabitants, a quality that concerns many aspects such as their health, the quality of the air they breathe, the temperatures generated by the city’s architecture, the size of green spaces, the noise level, etc. Big cities must achieve a balance between all these factors that influence the lives of their inhabitants. A lot of data and information about everything that can influence the quality of life is collected and analyzed. One of the elements that can help transform big cities by improving the quality of life, optimizing resources and reducing environmental impact for a smarter and greener future is Machine Learning (ML). ML is about developing algorithms that allow computers to learn from data and make predictions or decisions without explicit programming. The purpose of this paper is to highlight the role that ML can play in improving the quality of life in big cities and the contribution it can make to their sustainable development. The sections of the paper aim to identify and describe the aspects that concern the environment in big cities, the specific aspects of ML as well as the optimization that ML can bring through its use. Finally, the use of ML for a city-related data set is exemplified. Keywords: environment, machine learning, big cities, data mining